(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The evaluation of vibration magnitude created by a staggered drilled holes pattern in a limestone quarry in Okpella, Edo State, Nigeria was investigated. The SLAM STICK X rendered the time spectrum into frequency spectrum which is then converted into velocity to determine the sites constants which are related to the rock geological factor. The generated equation from the site constants is a guide for blasters when using staggered drilled holes pattern in limestone quarry. The study established the specific site constants (k and B) as 721.6 and -1.52 respectively for vibration generated in Okpella limestone mine to predict blast-induced vibration and safe distance. A predictive model developed for the studied quarry based on these constants, gave a safe distance of 102 meter when an explosive weight of 420 kg was exploded. The values generated from the equation generated from the model was compared with the Australian Standards to decide the weight to be used and distance between shot point and observation point to determine the safety of structures.